Validity of Adjuvant! Online in older patients with stage III colon cancer based on 2967 patients from the ACCENT database. Issue 6 (November 2016) - Papamichael, Demetris; Renfro, Lindsay A.; Matthaiou, Christiana; Yothers, Greg; Saltz, Leonard; Guthrie, Katherine A.; Van Cutsem, Eric; Schmoll, Hans-Joachim; Labianca, Roberto; André, Thierry; O'Connell, Michael; Alberts, Steven R.; et al.
Abstract: Background: Adjuvant! Online is a tool used for clinical decision making in patients with early stage colon cancer. As details of the tool's construction are not published, the ability of Adjuvant! Online to accurately predict outcomes for older patients (age 70 +) with node positive colon cancer receiving adjuvant chemotherapy is unclear. Methods: Individual data from older patients with stage III colon cancer who enrolled into multiple trials within the ACCENT database were entered into the Adjuvant! Online program to obtain predicted probabilities of 5-year overall survival (OS) and recurrence-free survival (RFS). Median predictions were compared with known rates. As co-morbidities were not known for ACCENT patients, but required for calculator entry, patients were assumed to have either "minor" or "average for age" co-morbidities. Results: 2967 older patients from 10 randomized studies were included. When "minor" co-morbidities were assumed, the median predicted 5-year OS rate of 64% nearly matched the actual rate of 65%; when "average for age" co-morbidities were assumed, the median prediction dropped to 58%, outside the CI for the actual rate. On the other hand, assuming "minor" co-morbidities gave a median 5-year RFS prediction of 62%, outside the 95% CI for the actual rate of 58%, while assuming "average for age" co-morbidities yielded a better median prediction of 57%. Conclusion: Adjuvant! Online is reasonably accurate overall for predicting outcomes in older trial patients with stage III colon cancer, though accuracy may differ between 5-year RFS and 5-year OS predictions when a fixed degree of co-morbidities is assumed.